MuseumScouts: Exploring how schools, museums and interactive technologies can work together to support learning - Wishart, Jocelyn; Triggs, Pat (Computers and education, 2010)
In this paper we report on the successes and challenges of a creative project involving museums, schools and interactive technologies. The MuseumScouts project is EU Comenius 2.1 funded and involves teachers, teacher educators, museum staff, students and researchers from five European countries: Germany (Berlin and Munich), Lithuania (Vilnius), Portugal (Porto), Austria (Linz), and the UK (Bristol and London). The MuseumScouts project arises from a European-wide desire to bring schools and cultural and educational institutions such as museums of different kinds, art galleries, science centres and historic buildings, together in collaborative learning experiences. The project aims to develop learner-centred approaches in the ‘museum’ environment: learners use information they collect during authentic learning opportunities to design short interactive multimedia teaching presentations with collaborative authoring tools. The focus is on knowledge acquisition, transformation and communication. During a ‘museum’ visit students (mainly 10–19 year olds but also, in some cases, adult learners) research specific artefacts, using a range of devices, from pencil and paper to Smartphones, to gather information in the form of notes and photographs. They then work in teams to create interactive multimedia presentations about the artefacts to inform and quiz their peers. The authoring tool, ‘Evolution’, which underpinned the project enables students to collaborate and work online. The principle is of ‘learning by teaching’: the idea that considering how to convey to others what you have understood yourself is an important process for ‘deep’ learning. The project has been run with groups of students at least once in each partner country and twice in several. Countries implemented the project activities in different subject areas, at different stages in the school curriculum and with differing amounts of available time. Student motivation and engagement were notable in all contexts. We present a review of findings common to all the partners in order to share experiences of implementing this pedagogic approach.